Postcolonial Language Varieties in the Americas - Arbes, Deborah; Braga Mattos, Ana Paulla; Mazzoli, Maria; Perez, Danae; Rees, Iwan Wyn; Robbers, Maja; Schmalz, Mirjam; Schneider, Britta; Sippola, Eeva; Stolz, Christel; Stolz, Thomas (Koloniale und postkoloniale Linguistik ;, 2021)
In the Americas, both indigenous and postcolonial languages today bear witness of massive changes that have taken place since the colonial era. However, a unified approach to languages from different colonial areas is still missing.The present volume studies postcolonial varieties that emerged due to changing linguistic and sociolinguistic conditions in different settings across the Americas. The studies cover indigenous languages that are undergoing lexical and grammatical change due to the presence of colonial languages and the emergence of new dialects and creoles due to contact. The contributions showcase the diversity of approaches to tackle fundamental questions regarding the processes triggered by language contact as well as the wide range of outcomes contact has had in postcolonial settings.The volume adds to the documentation of the linguistic properties of postcolonial language varieties in a socio-historically informed framework. It explores the complex dynamics of extra-linguistic factors that brought about the processes of language change in them and contributes to a better understanding of the determinant factors that lead to the emergence and evolution of such codes.